Prevalence and risk factors of obstructive sleep apnea in depression: an observational retrospective study - Chen, Xiujuan; Qiu, Zhengfa; Hu, Changzhou; Liu, Zhiwang (Frontiers in Psychiatry, 2025)
BackgroundA substantial number of previous studies have concentrated on the prevalence of depression among patients with obstructive sleep apnea (OSA). However, research regarding the prevalence of OSA among patients with depression remains relatively scarce. The aim of this study was to determine the prevalence of OSA among patients with depression and to identify the associated risk factors.MethodA single-center retrospective chart review was conducted. The research focused on patients diagnosed with depression who were referred for a polysomnogram (PSG) during a one-year period. Patients were diagnosed with obstructive sleep apnea (OSA) if their apnea-hypopnea index (AHI) was ≥5. Using the PSG monitoring results, patients were classified into two distinct groups: the OSA group, consisting of 50 patients, and the non-OSA group, which included 109 patients. An in-depth analysis was subsequently conducted on the sleep architecture and factors associated with the risk of OSA.ResultsAmong the 159 depression patients who met the subject criteria, 31.4% were diagnosed with OSA. Statistically significant differences were observed between the OSA group and the non-OSA group in terms of sex, body mass index (BMI), smoking status, and lipid levels (all p<0.05). The PSG monitoring results indicated that both the duration of non-rapid eye movement stage 3 (N3) sleep and the percentage of N3 sleep relative to total sleep time (N3/TST) were markedly lower in the OSA group than in the non-OSA group, with a statistically significant difference (p<0.01). Statistically significant differences were observed between the two groups regarding the number of awakenings, arousal index (ArI), mean oxygen saturation, oxygen saturation nadir, and oxygen desaturation index (all p<0.01). Multiple logistic regression analysis indicated that advanced age (odds ratio [OR]=1.034, 95% confidence interval [CI]: 1.004-1.065, p=0.024), female sex (OR=0.378, 95% CI: 0.171-0.837, p=0.016), low-density lipoprotein cholesterol (LDL-C) (OR=1.946, 95% CI: 1.026-3.692, p=0.041), and BMI≥25.0 kg/m² (OR=3.434, 95% CI: 1.411-8.360, p=0.007) were factors associated with OSA among patients with depression.ConclusionOSA was prevalent among patients with depression. Risk factors for OSA included male sex, advancing age, a BMI≥25.0 kg/m², and elevated LDL-C levels.